Faktor-Faktor Yang Berhubungan Dengan Hipertensi Pada Ibu Hamil Di Rumah Sakit Permata Medika - Eny Sulistiyowati; Mudy Oktiningrum; Nella Vallen (Lembaga Pengembangan Kinerja Dosen, 2024)
Introduction: Hypertension in pregnancy can be influenced by several factors (multiple causes). Pregnant women with hypertension will feel more anxious than pregnant women who do not have comorbidities.Objective: to determine the factors associated with hypertension in pregnant women at Permata Medika Hospital. Method: using observational analytical methods with a cross sectional approach. Sample: The population in this study were 100 pregnant women at Permata Medika Hospital whose gestational age was 20-40 weeks with a sample of 50 respondents. Data collection was carried out using a questionnaire. The data analysis used is Chi-square analysis. Results: there is a relationship between body mass index and hypertension in pregnant women at Permata Medika Hospital with a p-value of 0.000 > 0.05. There is a relationship between age and hypertension in pregnant women at Permata Medika Hospital, there is no relationship between parity and hypertension in pregnant women at Permata Medika Hospital.